2003
DOI: 10.4049/jimmunol.170.4.1814
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Related Apoptosis-Inducing Ligand Mediates Tumoricidal Activity of Human Monocytes Stimulated by Newcastle Disease Virus

Abstract: The Newcastle disease virus (NDV) has antineoplastic and immunostimulatory properties, and it is currently clinically tested in anticancer therapy. However, the tumoricidal mechanisms of NDV tumor therapy are not fully understood. The results presented here demonstrate that NDV-stimulated human monocytes (Mφ) kill various human tumor cell lines and that this tumoricidal activity is mediated by TRAIL. In contrast to soluble TRAIL-R2-Fc, soluble CD95-Fc and TNF-R2-Fc showed only minimal blocking of the antitumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
97
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 32 publications
7
97
1
1
Order By: Relevance
“…Furthermore, it has been reported that type-I IFN cause rapid maturation of monocytes into TRAIL-expressing DC in SCID mice reconstituted with human PBL [30]. Supporting this concept, TRAIL up-regulation in NDV-infected monocytes could be abrogated by neutralization of type-I IFN [28]. Alternatively, TRAIL gene expression could be induced by viral proteins that activate NF-‹ B as recently demonstrated for the Tax protein of human T cell leukemia virus type I [31].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, it has been reported that type-I IFN cause rapid maturation of monocytes into TRAIL-expressing DC in SCID mice reconstituted with human PBL [30]. Supporting this concept, TRAIL up-regulation in NDV-infected monocytes could be abrogated by neutralization of type-I IFN [28]. Alternatively, TRAIL gene expression could be induced by viral proteins that activate NF-‹ B as recently demonstrated for the Tax protein of human T cell leukemia virus type I [31].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, expression of TRAIL was also increased at the protein level. Interestingly, several other viruses have been shown to induce TRAIL in monocytes or monocytederived DC conferring cytotoxicity to these cells: measles virus [26], human cytomegalovirus [27] and Newcastle disease virus (NDV) [28]. This effect could be mediated by virus-induced IFN- § , which has been shown to induce TRAIL expression in DC [29].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that NDV induces TRAIL on CD14 1 monocytes and on CD3 1 T cells. 13 The cell-mediated antitumor activity observed could therefore at least partially be mediated via TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…12 NDV was also shown to induce TNF-related apoptosis inducing ligand (TRAIL), which can mediate tumoricidal activity. 13 To further augment the immunogenicity of the NDVmodified autologous tumor vaccine (ATV-NDV), we constructed 2 bispecific single-chain Fv (bsscFv) antibody molecules that specifically bind to HN molecules and to either CD3 or CD28 molecules on human T lymphocytes. Their construction, production and binding characteristics have been described.…”
mentioning
confidence: 99%
“…The findings that (i) NK cells can mediate cytotoxicity by TRAIL (7,32,35,54,63,65,77), (ii) that IL-15 potentiates NK cell cytolytic activity, and (iii) that TRAIL has intrinsic activity against a variety of virally infected targets (5,11,14,17,21,34,41,45,46,73,76) suggest a role for IL-15 to potentiate TRAIL-mediated NK cell viricidal activity. We demonstrate that PBL and resting memory cells from infected individuals express high levels of the TRAIL death receptors and undergo cell death following TRAIL treatments (29,33,45), suggesting that these cells are potential targets for TRAIL killing.…”
Section: Discussionmentioning
confidence: 99%